Analysis of Conditions for the Development of Language Culture of Students in Education - Iskandarova Aybibi Raximbayevna; Amanlikova Nafisa Raxmatullayevna (Genius Journals, 2023)
Our article provides an overview of early, important, and recent developments in thinking about language education and culture, and offers perspectives for future research and practice. Historically, language education has often been targeted at indigenous and immigrant peoples to eradicate perceived undesirable cultural practices and weaken the ties of cultural or ethnic identity. Later, differences in language origins were harmfully associated with so-called cultural deficits and used as a justification for language re-education. More recently, the fields of anthropology, educational research, and applied linguistics have taken up the challenge of rethinking language teaching as a means of affirming and preserving culture and helping language learners to build crosscultural connections. Students, future specialists, should not only master knowledge. You should implement them in situations of oral and written business communication: formulate the problem, defend your point of view, justify the arguments, and keep the documentation properly
Keywords: Competitiveness; represent points; phenomenon; norms